Mechanism of tomato extract against platelet over-activation in diabetic atherosclerosis - CAI Huan; JIANG Yan; LIU Jingqin; TAN Sijie; QI Feng (Zhongguo shipin weisheng zazhi, 2022)
Platelet over-activation is one of the important mechanisms of atherosclerosis （AS） in diabetes mellitus. Dietary nutrient intervention plays an important role in the primary prevention and treatment of diabetes mellitus combined with AS. Studies have shown that the antiplatelet factor in tomato extract can inhibit platelet aggregation and activation in different environments. Its bioactive ingredient are nucleosides and derivatives and phenolic compounds， which retard the pathological progress of diabetes mellitus complicated with AS. This review aims to explore the mechanism of the antiplatelet effect of tomato extract， and to provide a theoretical basis for the prevention and treatment of diabetes mellitus complicated with AS.